Design A Controller To Control Fluorescent Lighting And Other Electrical Equipment In A Classroom Using Programmable Logic Controllers - Ang Shor, Lin Sherine (Universiti Sains Malaysia, 2006)
Programmable Logic Controllers (PLC) is widely used in almost any industrial applications in our modern world. In this project, the PLC is used to control dimming and ON/OFF control of fluorescent lights as well as other electrical equipments in a typical classroom. Sensors and switches are used as inputs to the PLC to determine the current condition is the classroom. This project offers great energy management control avoiding energy wastage by human carelessness as well as unnecessary over energy usage. Dimming control of fluorescent lights would not only allow energy saving but would also pro-long the life span of the fluorescent lights as well as ensuring a sufficient and comfortable level of light intensity in the classroom for the students. A small classroom model is considered in this project for fluorescent lights control. A Passive Infrared Remote (PIR) Motion Sensor is used as an input sensor to detect the presence or absence of people in the classroom; manual switches are also included in this project for special cases where the motion sensor malfunctions. Apart from that, light intensity sensors are also implemented using light dependent resistors (LDR) to obtain the luminance level of the environment as well as allowing dimming control of the fluorescent lights in the classroom. Besides that, a light sensor is also implemented to detect the projector current status to allow proper lighting control. All these input sensors and switches will serve as input signals to the PLC making proper lighting control possible. Proper lighting controls will be sent through the PLC I/O ports to the hardware devices. For dimming control of fluorescent lamps, the normal ballast must be replaced with dimming ballast. Although dimming ballasts involves rather new technology, tedious and complex design procedures as well as in depth knowledge in ballast design, by using the Ballast Designer software (BDA) its steps are significantly reduced and simplified. The ballast designed in this project is done using the dimming ballast IC IR21592 from International Rectifier. This ballast is designed to suite a single T8 36W fluorescent lamp from a 240Vac input voltage source. This project shows how proper fluorescent lighting control and energy management in a classroom can be derived through a proper interface with minimum software and hardware connections.